Factors Affecting High-Tech Application Behavior in Livestock Industry in the South Central and Central Highlands Regions, Vietnam - Hoang, Thi Hoai Huong; Tran, Thi Thanh Nhan; Le, Thi Yen (Research on World Agricultural Economy, 2025)
The application of high technology in agricultural activities contributes to increased productivity, improved production efficiency, enhanced product quality, cost savings, reduced production costs, and, potentially, environmental protection. However, the development and adoption of high technology in agricultural production–particularly in the livestock sector–remain significant challenges in Vietnam. This study was conducted to identify and analyze the factors influencing the behavior of high-tech adoption in livestock farming in the South Central Coast and Central Highlands regions of Vietnam. The data used in this study were collected through a survey of 297 livestock farmers in the South Central and Central Highlands regions of Vietnam. It utilized SPSS 22 and AMOS software to evaluate the factors influencing the adoption of high technology in the livestock industry. The analysis revealed a direct positive relationship between several factors–expected efficiency, expected effort, favorable conditions, social influence, trade–off value, limitations of traditional production, and environmental awareness–and the intention to use high technology. Additionally, favorable conditions were positively linked to both the intention to use high technology and the actual behavior of adopting it in livestock farming. Based on these findings, the study offers several recommendations for localities, farms, and livestock companies to promote the application of high technology in production, particularly in the South Central and Central Highlands provinces of Vietnam.